1992
DOI: 10.1038/360674a0
|View full text |Cite
|
Sign up to set email alerts
|

Projection domains of MAP2 and tau determine spacings between microtubules in dendrites and axons

Abstract: Neurons develop a highly polarized morphology consisting of dendrites and a long axon. Both axons and dendrites contain microtubules and microtubule-associated proteins (MAPs) with characteristic structures. Among MAPs, MAP2 is specifically expressed in dendrites whereas MAP2C and tau are abundant in the axon. But the influence of MAP2, MAP2C and tau on the organization of microtubule domains in dendrites versus axons is unknown. Both MAP2 and tau induce microtubule bundle formation in fibroblasts after transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
426
3
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 551 publications
(453 citation statements)
references
References 24 publications
18
426
3
6
Order By: Relevance
“…The rather short (≈100 aa) semi‐structured repeat domain bears some transient β‐sheet propensity, and its flanking proline‐rich regions have been identified as relevant for microtubule binding (MTB; Mukrasch et al , 2007). The N‐terminal half of tau stays unstructured when projecting from MTs (Chen et al , 1992) and, in this context, a brush of N‐terminal domains on MTs may have mechanical relevance for MT spacing (Chen et al , 1992). Other studies showed a role of the N‐terminal half of tau as binding site for kinases with SH3 domains, such as Fyn and MARK (Reynolds et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The rather short (≈100 aa) semi‐structured repeat domain bears some transient β‐sheet propensity, and its flanking proline‐rich regions have been identified as relevant for microtubule binding (MTB; Mukrasch et al , 2007). The N‐terminal half of tau stays unstructured when projecting from MTs (Chen et al , 1992) and, in this context, a brush of N‐terminal domains on MTs may have mechanical relevance for MT spacing (Chen et al , 1992). Other studies showed a role of the N‐terminal half of tau as binding site for kinases with SH3 domains, such as Fyn and MARK (Reynolds et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In neither case are MTs attached to the centrosome or any known nucleating structure. In addition, cross sections through neuronal processes have shown that the MTs are not randomly distributed but are regularly spaced by cross-bridges ranging in length from ~65 nm in dendrites to ~25 nm in axons (Chen et al, 1992).…”
Section: Neuronal Cellsmentioning
confidence: 99%
“…Tau, which is preferentially found in axons (Binder et al, 1985), and MAP2, which is preferentially found in dendrites (Bernhardt and Matus, 1984), might bundle MTs because overexpression of these proteins in insect cells generates processes that have MT-MT spacings that reflect the size of the MAP (Chen et al, 1992). Nonetheless, mice lacking either tau or MAP2 have relatively normal neurons, which suggests that other factors are involved (Harada et al, 1994;Teng et al, 2001).…”
Section: Mt Bundlingmentioning
confidence: 99%
“…It could act as a spacer, or interact with other proteinsfor example, signaling molecules such as kinases, phosphatases, heat shock proteins (HSPs) and other cytoskeletal elements. [22][23][24][25] Because MAPs and microtubule motors both bind to the surface of microtubules, they can potentially interfere with each other. Thus, the overexpression of tau can retard motor-dependent transport, particularly in the anterograde direction.…”
Section: Figmentioning
confidence: 99%